(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Acronine is a natural alkaloid molecule with an acridine structure that have potent power to stop the progression of tumor/cancer cells but its therapeutic potential for clinical purpose is significantly hindered by its poor solubility due to its hydrophobic nature. The recent study is focus to establish a novel natural polymeric platform of Acronine loaded Eudragit-E nanoparticles (AENPs) using nanoprecipitation technique. The AENPs were experimentally characterized for encapsulation potential, size distribution, morphology of nanoformulation, zeta potential, drug release rate evaluations, and FTIR. The drug or Acronine release profile was evaluated for in vitro antioxidant and anticancer potential. Experimentally found that AENPs possess particle size within the range of 20 - 45 nm and having encapsulation efficiency of 56.37%. Furthermore, Eudragit-E at 2.5 mg/ml and Pluronic at 0.6% w/w were competent to produce isolated and free flowing nanoparticles. The in vitro anti-cancer assay of AENPs demonstrated inhibition of cancer cells to a greater extent and induced programmed cell death in Hela cell lines as compared to drug particles alone. These findings suggest the utilization of acronine entrapped Eudragit-E nanoparticles as advance drug delivery tool to combat cancer.